Textured grinding wheels: A review. (October 2016) - Li, Hao Nan; Axinte, Dragos
Abstract: Textured grinding wheels (TGWs) are wheels that have both specially-designed active and passive grinding areas on their geometrically active surfaces. The active area allows TGWs to perform the intermittent grinding process such that total wheel-workpiece contact time, average grinding forces and temperature in the cutting zone can be reduced. The passive area (or textures) refers to the non-grinding area where no grain is located at and the main functions of it include serving as reservoirs to transport more coolants/lubricants into the grinding zone and providing larger chip disposal space. With the increasingly demanding requirements from industries, the continuous evolution of TGWs has been enforced. However, to the best of the authors' knowledge, no comprehensive review on TGWs has been reported yet. To address this gap in the literature, this paper aims to present an informative literature survey of research and engineering developments in relation to TGWs, define and categorise TGW concepts, explain basic principles, briefly review the concept developments, discuss key challenges, and further provide new insights into understanding of TGWs for their advanced future engineering applications. Highlights: The studies related with textured grinding wheels (TGWs) have been reviewed. The definition, classification, and basic principle of TGWs have been given. Texture geometry, dimension and texturing methods have been analyzed. Promising future directions related with TGWs have been given.